Left bundle branch pacing with normal paced QRS axis produce more physiological left ventricular lateral wall depolarization than its pacing resulting in heart axis deviation. (19th May 2022) - Curila, K; Jurak, P; Jastrzebski, M; Sussenbek, O; Waldauf, P; Halamek, J; Stros, P; Smisek, R; Znojilova, L; Plesinger, F; Leinveber, P; Viscor, I; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic Background: Left bundle branch pacing is defined as the pacing of the trunk or its proximal fascicles, usually with septal myocardial pacing at low output. It preserves physiological left ventricular activation; however, it is unknown if there is a difference between captures with normal or deviated axes and pacing in proximal vs. distal locations. Objective: To study ventricular activation during nonselective LBB pacing (nsLBBp) resulting in different paced QRS axes and proximal vs. distal pacing positions using ultra-high-frequency ECG (UHF-ECG). Methods: This was a retrospective analysis of patients with bradycardia in which nsLBBp was archived during an implant procedure, and UHF-ECG analysis of ventricular activation was performed. nsLBBp captures were classified according to paced QRS axis as with superior (-30°;-90°), normal (-29°;60°), or inferior (61°;120°) axis deviation and proximal (LBbpo to ventricular EGM signal distance ≥ 26 ms) vs. distal (LBBpo to ventricular EGM signal distance < 26 ms). UHF-ECG electrical dyssynchrony parameters – e-DYS (difference between the first and last ventricular activation), local depolarization durations in precordial leads (V1-V8d), and their mean value (Vdmean) were calculated. Results: We have studied 79 nsLBBp, of which 35 had superior, 28 normal, and 16 had inferior paced QRS axes. There was no difference in LBBpo to V distance, QRSduration, V5 RWPT, or e-DYS (-27 ms vs. – 22 ms vs. -25 ms for superior vs. normal vs. inferior axes; p = NS) between them. However, nsLBBp with normal paced QRS axis had shorter Vdmean (43 ±6 ms) compared to captures with superior (48 ± 7 ms) and inferior axis deviation (48 ± 6 ms); p < 0.05. It was mainly due to shorter V7-8d during nsLBBp with normal axis (mean difference of - 10 ms; p < 0.05) than in captures with superior or inferior axes. No difference in any of the studied parameters was noted when comparing proximal vs. distal pacing locations. Conclusion: Nonselective capture of the left bundle branch resulting in normal paced QRS axis produces more physiological LV activation compared to captures with superior or inferior axes deviations.